(untitled) (Research, Society and Development, 2017)
This study is an experience report that aims to describe a nursing academics experience in participating in an extension project aimed at adolescents’ health. The extension project entitled "Adolescer Bem” offered during the discipline of child and adolescent health at José do Rosário Vellano University, Alfenas-MG, worked together with the Health in School Project, in a public school. In view of the vulnerabilities in which adolescents remained exposed, such as lack of knowledge about the physical and psychological changes of adolescence; Concern exacerbated with body image; Fear of the future; Bullying among peers; Difficulty in family relationships; Limited educational training regarding the deleterious effects of the use of alcohol and other drugs, as well as with regard to sexually transmitted diseases, teenage pregnancy and the use of contraceptive methods, educational activities were carried out in order to promote knowledge autonomy in these adolescents. The educational and innovative activities in the school issue enabled interaction between nursing academics and adolescents. It was concluded that the Adolescer Bem project subsidized reflective training in the work of the authors involved, as well as preventive education among adolescents.